2013
DOI: 10.3899/jrheum.131244
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Measures in Acute Gout: A Systematic Literature Review

Abstract: Objective Five core domains have been endorsed by Outcomes Measures in Rheumatology (OMERACT) for acute gout: pain, joint swelling, joint tenderness, patient global assessment, and activity limitation. The aim of this work was to evaluate instruments for these domains according to the OMERACT filter: truth, feasibility, and discrimination. Methods A systematic search strategy for instruments used to measure the acute gout core domains was formulated. For each method, articles were assessed by two reviewers t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…Consistent with the literature [8, 19, 36, 37], CE activities (both patient and clinician interviews and qualitative digital ethnography) identified pain as being the cardinal, defining symptom of gout, leading to a range of impacts on QoL. In particular, this study found that patients discussed severe debilitating flares of pain causing an inability to weight bear and an impact on physical functioning (e.g., difficulty walking), sleep, daily activities, and work (e.g., productivity) and social activities (e.g., missing/cancelling plans).…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with the literature [8, 19, 36, 37], CE activities (both patient and clinician interviews and qualitative digital ethnography) identified pain as being the cardinal, defining symptom of gout, leading to a range of impacts on QoL. In particular, this study found that patients discussed severe debilitating flares of pain causing an inability to weight bear and an impact on physical functioning (e.g., difficulty walking), sleep, daily activities, and work (e.g., productivity) and social activities (e.g., missing/cancelling plans).…”
Section: Discussionsupporting
confidence: 91%
“…Diagnostic criteria were completed each of the recruited patients accordingly GA (ACR 1997), RA (revised ACR 2010), AS (ACR1984). Visual analogue scales (VAS) 0–10cm were applied in GA (mean 4.07 ± 1.15) [ 13 ]. In RA composite disease activity measures included the clinical disease activity and 28 joint disease activities score (DAS28) mean value is 4.97 ± 1.12 [ 14 , 15 ] and in AS disease activity are decided as per ankylosing spnodolylitis disease activity score (ASDAS) mean value 2.97 ± 0.81 [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Five core domains have been endorsed by OMERACT for acute gout: pain, joint swelling, joint tenderness, patient global assessmen and activity limitation. 47 The Gout Special Interest Group is trying to identify domains of interest and is now evaluating a series of outcomes for features of chronic gout, such as serum uric acid level, physical measurement or digital photography of tophi and imaging modalities. 48,49 Gout-specific patient reported outcome instruments like the Gout Assessment Questionnaire (GAQ) were also developed that collect information about gout impact, assessing pain, well-being, productivity and treatment satisfaction.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Lesinurad 67 is a urate transport inhibitor (inhibits URAT 1 and OAT 4 in renal tubules 47 ) for treating hyperuricemia associated with gout in patients who have not achieved target serum uric acid levels with a xanthine oxidase inhibitor alone. It very recently received US Food and Drug Administration approval.…”
Section: Treatmentmentioning
confidence: 99%